Microstructure and phase transformations in laser clad CrxSy/Ni coating on H13 steel. (March 2015) - Lei, Yiwen; Sun, Ronglu; Tang, Ying; Niu, Wei
Abstract: Laser cladding was carried out onto H13 steel with preplaced NiCrBSi+Ni/MoS2 powders using CO2 laser under the optimized experimental parameters of laser power 2 kW, scanning velocity 6 mm/s and laser beam diameter 3 mm. An X-ray diffractometer and scanning electron microscope with energy dispersive spectroscopy were applied to analyze the microstructure and phase compositions of the coating. Thermodynamic calculation was performed with Thermo-Calc software on the basis of a commercially available Ni-based Alloys׳ database. The experimental results show that MoS2 decomposed and S reacted with Cr to form nonstoichiometric Cr x S y during the laser cladding process. The coating consists of spherical Cr x S y particles, primary γ-Ni dendrite, interdendritic eutectic (γ-Ni+NiMo) and precipitated NiMo. The precipitated NiMo was fine and uniformly distributed in primary γ-Ni dendrite. The calculated results and experimental data indicate that the solidification process in the coating during laser cladding process was liquid→liquid+Cr x S y → liquid+Cr x S y +γ-Ni→liquid+Cr x S y +γ-Ni+ eutectic (γ-Ni+NiMo). A solid state phase transformation (fine and uniformly distributed NiMo precipitated from γ-Ni) occurred after the solidification process. The calculations agree well with the experimental data and it is helpful to understand the phase transformation and microstructure evolution in the coating. Highlights: Laser clad Cr x S y /Ni coating was obtained on H13 steel with NiCrBSi+Ni/MoS2 powders. Large quantity of Cr x S y solid lubricant was in situ formed in Cr x S y /Ni coating. The coating consisted of Cr x S y, γ-Ni, eutectic (γ-Ni+NiMo) and precipitated NiMo. Phase transition and microstructure evolution were discussed based on calculation.